Homeopathic Remedies in COVID-19: Prognostic Factor Research - Manchanda, Raj Kumar; Miglani, Anjali; Gupta, Meeta; Meena, Baljeet Singh; Chadha, Vishal; Joseph, Franco; Kalsi, Amrit; Konthembath, Pramod; Sharma, Kavita; Rama, Kamsali Nadigadda; Kaur, Prabhjeet; Thavarayil Kannoth, Jithesh; Nagrath, Cheshta; Jethani, Anju; Nellikka Aniyeri, Shajimol; Chawla, Anu; Ray, Malaya Kumar; Ghuliani, Manjula; Kudiyarasu, Ram Kumar; Naskar, Shruti; Bala, Sudha; Sharma, Brender (Homeopathy, 2021)
Background/Objective Coronavirus disease 2019 (COVID-19) is a new disease; its clinical profile and natural history are evolving. Each well-recorded case in homeopathic practice is important for deciding the future course of action. This study aims at identifying clinically useful homeopathic remedies and their prescribing symptoms using the prognostic factor research model.Methods This was an open-label, multi-centric, observational study performed from April 2020 to July 2020 at various public health care clinics. The data were collected prospectively from clinical practice at integrated COVID-19 care facilities in India. Good-quality cases were selected using a specific set of criteria. These cases were analyzed for elucidating prognostic factors by calculating the likelihood ratio (LR) of each frequently occurring symptom. The symptoms with high LR values (>1) were considered as prescribing indications of the specific remedy.Results Out of 327 COVID-19 cases reported, 211 met the selection criteria for analysis. The most common complaints were fatigue, sore throat, dry cough, myalgia, fever, dry mouth and throat, increased thirst, headache, decreased appetite, anxiety, and altered taste. Twenty-seven remedies were prescribed and four of them—Arsenicum album, Bryonia alba, Gelsemium sempervirens, and Pulsatilla nigricans—were the most frequently used. A high LR was obtained for certain symptoms, which enabled differentiation between the remedies for a given patient.Conclusion Homeopathic medicines were associated with improvement in symptoms of COVID-19 cases. Characteristic symptoms of four frequently indicated remedies have been identified using prognostic factor research, findings that can contribute to accurate homeopathic prescribing during future controlled research in COVID-19.
Keywords: COVID-19; homeopathy; prognostic factor research; likelihood ratio